Groundings for a General Theory of the Economy (JEL - AO) - Kolev, Tsvetan (Research Papers, 2005)
The main idea and goal of the study is the constructing of the object indication of the general theory of the economy (GTE). The scientific hypothesis is based on the GTE as a metatheory that is unifying sciences that have as a common object of research into the economy. In the first part of the study – the contemporary economy as a research object, the concepts “economy” and “economics” are specified. With the first concept - economy is defined as an object of research by many sciences, including economics, and with the second - the economy as a science (economics). Next there is a definition of the economy as a concept and its contemporary clarification and its impact on society. In the second part – initial principles of the GTE, a brief historical article about the stages of development and classification of sciences is made and also examples from the practice are given. In this part is grounded the use of the concept metatheory and the approach from the point of view of analytical philosophy for the cognitive assertions as formal, informal and basic. Further exposition is subordinated to the following logic determination of the fundamental formal assertion as a leading element of the GTE (the behavior of the economic subjects), formulation of a common subject matter of the GTE and finally, a classification of the sciences within the framework of the GTE as a metatheory. Presented grounds of the GTE and its structure may serve the development of the science relief in scientific research into the economy, revealing new scientific fields, forming the science policy. If we present the structure of the GTE as graph, then it is possible to project interaction between sciences in the structure of the GTE on the background of axes of general scientific fields and their probable projection in the future. This is a goal of the following scientific study. Now it may safely be said only that the key for development of the GTE and in particular of economics is the implementing of research by the experts in all sciences that have the economy as a common object of research.